TWO NEW SPECIES AND TWO NEW VARIETIES OF COLUMNEA (GESNERIACEAE) (2015)
In this paper two new species of Gesneriaceae (genus Columnea) are described and illustrated. Columnea chocoensis is distributed in the Colombian departments of Chocó and Valle del Cauca, while its variety, C. chocoensis var. altaquerensis is restricted to the Department of Nariño, Colombia. Columnea stilesiana was found in La Serranía de Los Paraguas located in the Cordillera Occidental between the Chocó and Valle del Cauca Departments in Colombia. Further, Columnea archidonae is here considered a variety of C. ericae; Columnea ericae var. archidonae is distributed in Colombia and Ecuador, in forests at elevations higher than those in which the typical variety is found.